Proceedings of the 2014 ACM Conference on Web Science 2014
DOI: 10.1145/2615569.2615700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of visual attributes on online image diffusion

Abstract: Little is known on how visual content affects the popularity on social networks, despite images being now ubiquitous on the Web, and currently accounting for a considerable fraction of all content shared. Existing art on image sharing focuses mainly on non-visual attributes. In this work we take a complementary approach, and investigate resharing from a mainly visual perspective. Two sets of visual features are proposed, encoding both aesthetical properties (brightness, contrast, sharpness, etc.), and semantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 35 publications
(43 reference statements)
2
25
2
Order By: Relevance
“…Second, we see that social features alone produce better prediction results than image features alone. This corroborates many previous findings (e.g., [8,22,33]), which showed that social features are more important than image features for content popularity prediction. In our case, we are predicting the diffusion path, which is a much more difficult problem, and when no social features are used, it is impossible to say precisely how an image will be propagated through a social network.…”
Section: Per-node Diffusion Prediction Accuracysupporting
confidence: 92%
See 1 more Smart Citation
“…Second, we see that social features alone produce better prediction results than image features alone. This corroborates many previous findings (e.g., [8,22,33]), which showed that social features are more important than image features for content popularity prediction. In our case, we are predicting the diffusion path, which is a much more difficult problem, and when no social features are used, it is impossible to say precisely how an image will be propagated through a social network.…”
Section: Per-node Diffusion Prediction Accuracysupporting
confidence: 92%
“…A large number of recent efforts have explored ways to predict content popularity, including for images [7,8,10,14,22,33], videos [26], GitHub repositories [5], blogs [1], memes [36], and tweets [18,19,25,28], by combing content features with user social features. In contrast to these prior work, which mainly focus on predicting a popularity score (e.g., number of shares) of the content, we aim to predict the entire content diffusion path through the social network, which is a much more challenging task.…”
Section: Related Workmentioning
confidence: 99%
“…Various content and information can be the subject of diffusion within social networks, including images (Totti et al 2014), video (Boynton 2009;Nelson-Field, Riebe, and Newstead 2013), news (Yang and Counts 2010), rumours (Jin et al 2013), information about promotions and offers (Leskovec, Adamic, and Huberman 2007), virtual goods in virtual worlds, and special effects that can be applied to avatars, hair styles, or clothing (Bakshy, Karrer, and Adamic 2009;Huffaker et al 2011).…”
Section: Related Workmentioning
confidence: 99%
“…Information spreading processes are a basement of viral marketing [1], rumours [2], social and political changes [3], innovation adoption [4] and other initiatives with emotional appeal [5]. Possible types of contents propagated within electronic systems include texts [6], concepts [7], video material [8], images [9] and marketing messages [10]. Research in this area is, among others, related to information flow within the networks [11], factors affecting performance of marketing campaigns [12] and the selection of highly influential nodes [13].…”
Section: Introductionmentioning
confidence: 99%